Design and Implementation of an Electrical Lift Controlled using PLC - Mohammed Hasan Ali (International Journal of Electrical and Computer Engineering (IJECE), 2018)
This paper represents the possibility of controlling an electrical elevator model using PLC and studying some parameters to ensure its work, this model have been designed and constructed to perform a completed elevator work in an automating technique according to its programming and controlling method that making the connecting much more easier and safer than real relays and complicated wiring method. As well as the small DC motor drive (gear box) electrical motor that used  to drive the elevator cabinet which made the transition from floor to floor much smoother and much efficient than the traditional elevators.